Water Deficit Irrigation of Robusta Coffee Under Nursery Conditions in Sultan Kudarat, Philippines - Evasco, Rhealiza; Marcelino, Junito (Journal of Interdisciplinary Perspectives, 2025)
Robusta Coffee (Coffea canephora) is sensitive to water deficit, and its production is increasingly vulnerable to climate change, requiring the selection of drought-tolerant varieties. The study aimed to evaluate the growth response of four "France de Torino" clones (FRT 07, FRT 11, FRT 23, FRT 65) developed by Nestlé's Research and Development facility and three farmer-selected varieties (FRV-B, FRV-SNA, FRV-K) under stress conditions by withholding irrigation for 7, 14, and 21 days using a completely randomized design (CRD) with factorial treatment combinations. Growth responses were assessed based on leaf scorching, plant height, stem girth, number of leaves, soil moisture content, percentage of plant recovery, and biomass accumulation. Temperature and relative humidity (RH) were monitored to assess microclimatic effects. Results showed that prolonged drought stress reduced plant height (from 43.78 ± 4.21 cm at 7 days to 29.88 ± 3.42 cm at 21 days) and number of leaves (from 28.6 ± 3.4 to 15.8 ± 2.2), and increased leaf scorching (from 5.12 ± 1.38 to 21.32 ± 2.94). Among clones, FRT 23 had the highest average plant height (27.44 cm) under stress, while FRV-SNA exhibited the most incredible resilience across metrics, including the highest recovery rate (91.67%) and biomass accumulation (wet: 37.33 g; dry: 17.83 g). ANOVA revealed that drought stress significantly affected the growth parameters (p < 0.0001), while clone type influenced stem girth and recovery rate. Environmental monitoring revealed that inside the screenhouse, temperature reached a mean of 34.09°C, with relative humidity averaging 67%. Pearson's correlation showed strong inverse relationships between RH and inside screenhouse temperature (r = -0.9279, p < 0.001). Regression analysis indicated that temperature explained 86.1% of RH variability (Adj R² = 0.8605). Plants under 50% shade netting experienced moderated microclimates, supporting better growth under stress. The results were essential to improve the variety selection and water management strategies, ensuring long-term productivity and resilience of coffee in drought-prone areas.